The effect of nitrogen fertilizer on nutrient composition and in vitro digestibility of kenaf (Hibiscus cannabinus) - Abdul Aziz, Muhammad Salman (2015)
Feedstuff is an important input to sustain livestock production. In Malaysia, the nutrients from feedstuffs for ruminants, especially forages, often inadequate. A supply of good quality forages is necessary in order to meet ruminant nutrient requirements. This study was conducted to compare the effect of different levels of inorganic nitrogen fertilizer on nutrient compositions and in vitro digestibility of kenaf (Hibiscus cannabinus). There were five different levels of additional inorganic nitrogen fertilizer (urea: 0, 20, 40, 60, 80 Kg/ha) and were given to Kenaf V36 which initially on NPK (15:15:15) fertilizer. Kenaf V36 seeds were obtained from National Kenaf and Tobacco Board and used as planting materials. The treatments, which is the fertilization was applied twice, at the 10th and 20th day after planting respectively. Kenaf were watered manually 2 times a day by using hose pipe. The kenaf was harvested at the fifth week of age and analysed for dry matter yield (DM yield), plant height, proximate analysis, Neutral detergent fiber (NDF), acid detergent fiber (ADF) and acid detergent lignin (ADL). Digestibility of kenaf was estimated by using in vitro gas production procedure. The result shows that the DM yield ranged from 0.55 ton to 0.62 ton per hectare. There were significantly difference (P<0.05) in CP, NDF and ash of kenaf fertilized with different levels of inorganic nitrogen fertilizer. There were highly significance difference (P<0.01) in plant height, DM content and gas production of kenaf fertilized with different levels of inorganic fertilizer application. It was observed that the percentage of crude protein was the highest (20.59%) when the kenaf was fertilized with urea at the rate of 80 Kg/ha but the increase rate of CP started to decline at 40 Kg/ha. However, under the experimental conditions, the expected CP was not achieved because variety and light levels can affect the nutrient composition of kenaf.